Social Cohesion in the MUI Fatwa on Religious Tolerance: A Durkheimian and Parsonsian Socio-Legal Analysis - Saputra, Refki (Universitas Islam Negeri Sumatera Utara, 2026)
This article examines the Indonesian Council of Ulama’s (MUI) fatwa on religious tolerance in the celebration of other religious holidays from a socio-legal perspective informed by Émile Durkheim’s theory of social solidarity and Talcott Parsons’ AGIL framework. It analyzes how the fatwa functions as a religious norm in maintaining social cohesion while negotiating tensions between religious identity and Indonesia’s plural social reality. Using qualitative document analysis, this study draws on the official MUI fatwa on religious tolerance and relevant scholarly literature on Islamic law, sociology of law, and social integration. The findings show that the fatwa operates as a normative mechanism that reinforces internal religious solidarity while enabling selective forms of social integration in a multireligious society. From a Durkheimian perspective, the fatwa seeks to preserve mechanical solidarity by safeguarding collective religious boundaries, while also acknowledging the need for organic solidarity in a plural context. Through Parsons’ AGIL framework, the fatwa fulfills adaptive, integrative, and latency functions by regulating tolerance and preserving religious values. The study contributes theoretically by advancing a socio-legal understanding of Islamic fatwas as social institutions mediating religious norms and social cohesion in plural societies.